Advances in mathematical methods for electromagnetics - Kobayashi, Kazuya; Smith, P. D. 1955- (Institution of Engineering and Technology, 2020)
This book covers recent achievements in the area of advanced analytical and associated numerical methods as applied to various problems arising in all branches of electromagnetics. The unifying theme is the application of advanced or novel mathematical techniques to produce analytical solutions or effective analytical-numerical methods for computational electromagnetics addressing more general problems. Each chapter contains an outline of its topic, discusses its scientific context and importance, describes approaches to date, gives an exposition of the author's approach to the problem tackled in the chapter, describes the results, and concludes with a discussion of the range or class of problems where the techniques described work most appropriately and effectively. Intended primarily for researchers in the fields of electrical engineering, mathematics, physics and related disciplines, the book offers systematic and thorough coverage of this complex topic. It is hoped that the book will help to stimulate further investigation and discussion of the important problems in electromagnetics within this research community.
Keywords: Electromagnetic theory -- Mathematics.; Electromagnetism -- Mathematics.; elektronické knihy; electronic books